Arising issues in the execution of heritage conservation projects : collective reflections from case studies in Ireland / Muhammad Firzan … [et al.] - Firzan, Muhammad; Keumala, Nila; Zawawi, Rodiah; Ahmad, A Ghafar (Faculty of Architecture, Planning & Surveying, 2015)
Apparently, conservation agenda around the globe is getting more significant nowadays. In the quest to safeguard and sustain invaluable heritage assets remaining today, it is evident that more new: guidelines being regulated, approaches being introduced, courses being offered, and, growing interests being projected. Architecture discipline which melds together different areas such as: history, humanity, science, art, and technology, has emerged a new branch of specialization known as built heritage conservation. Realising the importance of Western’s experience as precedence for the relatively new Malaysian conservation industry, this paper collectively highlights on the execution of built heritage conservation projects across Ireland. Through a series of reflection sessions shared by practitioners based on their involvements on respective case studies, this paper summarises four arising issues of: an enquiry on praxis and compliance of conservation doctrines, essentiality of engaging the public in decision-making process and volunteerism, obsolescence and dereliction of historical buildings and sites as the diseases to heritage tourism, and, achieving environmental sustainability demand through energy efficiency and building retrofitting. Prior insights and recommendations based on these arising issues are presented for the attention of heritage stakeholders and conservation actors of Malaysia.